Examining the Success Rates in Licensure Examination for Teachers: A Quantitative Focus on Bachelor of Elementary Education (BEED) Graduates - Salendab, Fahad A.; Cogo, Donald A. (Future Science / FSH-PH Publications, 2024)
This study examines the success rates of Bachelor of Elementary Education (BEEd) graduates from Sultan Kudarat State University (SKSU) – Kalamansig Campus in the Licensure Examination for Teachers (LET). This study utilized the descriptive-comparative research design that compares two variables to describe the differences. The study's respondents were the Bachelor of Elementary Education (BEEd) graduates of Sultan Kudarat State University – Kalamansig Campus who took the Licensure Examination for Teachers (LET) for elementary level from 2018 – 2023. The respondents were selected using the purposive sampling method, with 185 respondents. The data were analyzed using the t-test for paired samples, and the Statistical Package for Social Science (SPSS) was used to analyze the t-test. The study compares the overall passing percentage with national averages and analyzes the General Education and Professional Education scores. The findings indicate fluctuating performance, with BEED graduates performing better in General Education than in Professional Education. Despite a higher mean passing percentage than the national average, the study highlights the need for continuous improvement in curriculum and teaching strategies to enhance LET outcomes. The impact of the COVID-19 pandemic on exam preparation and administration is also discussed. Recommendations are provided for educational stakeholders to adopt innovative teaching methods and improve faculty development to increase licensure examination success rates